Whole-body adipose tissue multi-omic analyses in sheep reveal molecular mechanisms underlying local adaptation to extreme environments - Xu, Ya-Xi; Wang, Bo; Jing, Jia-Nan; Ma, Rui; Luo, Yan-Hui; Li, Xin; Yan, Ze; Liu, Ya-Jing; Gao, Lei; Ren, Yan-Ling; Li, Meng-Hua; Lv, Feng-Hua (Communications Biology, 2023)
The fat tail of sheep is an important organ that has evolved to adapt to extreme environments. However, the genetic mechanisms underlying the fat tail phenotype remain poorly understood. Here, we characterize transcriptome and lipidome profiles and morphological changes in 250 adipose tissues from two thin-tailed and three fat-tailed sheep populations in summer and winter. We implement whole-genome selective sweep tests to identify genetic variants related to fat-tails. We identify a set of functional genes that show differential expression in the tail fat of fat-tailed and thin-tailed sheep in summer and winter. These genes are significantly enriched in pathways, such as lipid metabolism, extracellular matrix (ECM) remodeling, molecular transport, and inflammatory response. In contrast to thin-tailed sheep, tail fat from fat-tailed sheep show slighter changes in adipocyte size, ECM remodeling, and lipid metabolism, and had less inflammation in response to seasonal changes, indicating improved homeostasis. Whole-genome selective sweep tests identify genes involved in preadipocyte commitment (e.g., BMP2, PDGFD) and terminal adipogenic differentiation (e.g., VEGFA), which could contribute to enhanced adipocyte hyperplasia. Altogether, we establish a model of regulatory networks regulating adipose homeostasis in sheep tails. These findings improve our understanding of how adipose homeostasis is maintained, in response to extreme environments in animals.